Ohmic heating: Factors affecting on its application in food processing - Loypimai, Patiwit; Moongngarm, Anuchita (Food Agricultural Sciences and Technology, 2018)
Ohmic heating (OHM) has gained much interest in the food industry as a novel thermal food processing technology which improves food quality and nutritional value as well as reducing both processing time and cost. OHM, also referred to as Joule heating, electrical resistance heating, and resistive heating is an alternative method of warming food by passing an electric current through a conductor. It has significant advantages over conventional heating including reduced heating time (rapid heat generation), uniform heating, reduced quality losses and diminished energy consumption. However, the successful application of OHM in food processing depends on several parameters including the electrical conductivity and specific heat capacity of the food materials, systematic design, product size, heat capacity and viscosity which were reviewed here.